Juvenile morphology: A clue to the origins of the most mysterious of mysticetes? - Marx, Felix; Buono, Mónica Romina; Fordyce, R. Ewan; Boessenecker, Robert W. (Naturwissenschaften)
The origin of the pygmy right whale (Caperea marginata) has long been one of the most vexing conundrums of marine mammal evolution. The extremely disparate skeletal structure ofCapereaand a patchy fossil record have left morphology and molecules at odds: whereas most morphological analyses allyCapereawith right whales (Balaenidae), most molecular studies instead suggest a close relationship with rorquals (Balaenopteridae) and grey whales (Eschrichtiidae). The morphological evidence supporting aCaperea-balaenid clade consists of several shared features of the skull and mandible, as traditionally observed in adult individuals. Here, we show that at least two of these features, the ascending process of the maxilla and the coronoid process, arise from substantially different precursors early during ontogeny and therefore likely do not represent genuine synapomorphies. Both of these juvenile morphologies have adult counterparts in the fossil record, thus indicating that the ontogenetic variation in the living species may be a genuine reflection of differing ancestral states. This new evidence contradicts previous morphological hypotheses on the origins ofCapereaand may help to reconcile morphological and molecular evidence. Fil: Marx, Felix. University of Otago; Nueva Zelanda Fil: Buono, Mónica Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagonico; Argentina Fil: Fordyce, R. Ewan. University of Otago; Nueva Zelanda Fil: Boessenecker, Robert W. University of Otago; Nueva Zelanda